Aqueous biphasic systems composed of ionic liquids and polysaccharides - Carvalho, Sara Ferreira (2013)
Aiming at finding more biocompatible and environmentally-benign separation processes, aqueous biphasic systems composed of ionic liquids can be envisaged as an alternative and advantageous approach for the extraction and purification of the most diverse biomolecules. In this work, the main goal consisted on the study of the ability of polysaccharides, as a benign alternative over inorganic salts typically used, to form aqueous biphasic systems with ionic liquids. To this aim, the phase diagrams and respective compositions of the two phases in equilibrium for ternary systems consisting of several ionic liquids, water, and polysaccharides were determined at 298 K. By the combination of different families of ionic liquids, achieved by a representative variety of cations and anions, with dextrans and maltodextrins, it was possible to infer on the effect of the IL structural characteristics, as well as on the polysaccharides molecular weight through the formation ability of aqueous two-phase systems. Finally, and to ascertain on the potential application of these new systems such as extraction techniques, some of them were also used and evaluated regarding their aptitude to extract amino acids. The use of polysaccharides, namely dextran and maltodextrin, as salting-out molecules to form aqueous biphasic systems with ionic liquids was the main focus of this work. It was demonstrated here, for the first time, that a new class of aqueous biphasic systems composed of ionic liquids and polysaccharides can be formed while contributing to the development of more efficient and sustainable separation and purification techniques. These systems can be also seen as promising routes in the improvement of biotechnological processes which increasingly tend to be decisive in industry.